Pedagoška psihologija za učitelje: izbrane teme - Košir, Katja (2017)
Educational Psychology for Teachers: Selected Topics. The present textbook represents a review of selected topics from educational psychology that teachers should know in order to effectively enhance learning in students. Initially, relations between theory, research, and practice as well as the role of scientific theories and research findings for teachers' effective work and professional development are presented. In additional chapters, crucial models and concepts related to learning, learning motivation, classroom management, social relations, bullying and effective communication are demonstrated. Based on scientific models and research findings, some key recommendations and directions for the enhancement of quality learning, constructive motivational orientation, effective classroom management and positive peer and teacher-students relations are offered. The textbook is designed for students of teaching courses; however, it could be relevant also for teachers who want to refresh their knowledge of educational psychology.
Keywords: educational psychology; teachers; learning; teaching; textbook